Simulation of soil water dynamics and rice crop growth as affected by bunding and fertilizer application in inland valley systems of West Africa - Worou, Omonlola N.; Gaiser, T.; Saito, Kazuki; Goldbach, H.; Ewert, F. (Elsevier, 2012)
Rice production in rainfed inland systems is constrained by rainfall distribution and the heterogeneity of the topography that frequently lead to runoff causing erosion and loss of nutrients especially nitrogen. The use of water-saving and nutrient management technologies such as bunding and fertilizer application could help farmers maintain soil moisture and reduce nutrient losses thereby increase rice production. This study used the crop model EPIC (Environmental Policy Integrated Climate) to assess soil water dynamics and rice crop growth as affected by bunding and fertilizer application in inland valley systems of West Africa. The model was parameterized using observed soil water characteristics and crop parameters and run against observation data collected from 2007 to 2010 in a factorial trial combining bund and fertilizer rate. Simulation of soil water condition was satisfactory for unbunded conditions with coefficients of determination (R2) from comparison between simulated and observed soil water content between 0.64 and 0.68 depending on soil depth. Depth of ponded water during the growing period was adequately predicted in three out of four years. Simulated LAI development, total aboveground biomass and grain yield compared well with field observations in unbunded plots, the MRE (mean relative error) of simulated yield was 6–18%. In bund plots in 2009 and 2010, the grain yield was overestimated by the model when no fertilizer was applied (MRE = 45%). Although negative effect of elevated iron concentration in the rice plant reduces the model performance, it was used to indicate effective effect of iron on the growth of crop the presence of bund in very wet year. The general use of the model for rainfed rice production at a large scale requires identification of areas with iron toxicity risk